Relação entre ciência e política na formação de intelectuais - Oliveira, Elisangela Lizardo de (2015)
Motivated by economic, political and social transformations occurred in the mid-twentieth century, Brazilian scientists and intellectuals has been present from the idealization to execution of the State modernization process. Considering them important figures in the development of national science and technology, this research aimed to investigate the relation between science and politics experiences in the formation of four notorious knowledge Brazilian intellectuals who acted in this process: Antonio Candido, Carlos Chagas Filho, Carolina Martuscelli Bori and Florestan Fernandes. To achieve the objectives, the formative school, academic, cultural, professional and political experiences of these intellectuals were investigated in attempted to identify the association between their scientific and political experiences as indispensable processes for the formation of critical consciousness. The research has focused on a documentary analysis, whose main source was the publication Cientistas do Brasil depoimentos, published by the Brazilian Society for the Progress of Science (SBPC) in 1998 as a result of 60 interviews with intellectuals scientists that has conducted their careers mostly in Brazilian universities, between the years 1930- 1950. The analysis finds in Critical Theory of Society, specifically in the elaborations of Theodor Adorno, Max Horkheimer and Herbert Marcuse, the basis to discuss the concepts of science, politics and formation. The results confirm generally speaking the elaborated hypotheses and suggest undissociated relation between science and politics in the formative experiences of the four individuals. As subjects of their historical time, the intellectuals lived discrepant experiences about access to culture. Although most of them have lived with the high bourgeois culture since childhood, also showed up deprivations of school formative experiences and overvaluation of child labor. The institutions: school, family and work, have marked their initial experiences, but it was the university experience, coupled with the environmental politics and scientific achievements to which they belonged, that more marked the formation of the critical consciousness of these intellectuals. It was also found that political action of the subjects were expressed in different ways: closely with governments, in scientific associations, as opinion forming and even parliamentary action have being present in their actions; both breaking demonstrations with the determinations of the administered society, as integrating to the ideology of technological rationality